Management of Conjunctivitis (Eye Flu) Epidemic - Homeopathic Perspective from the Experience of Recent Delhi Epidemic (Homoeopathy for All, 2023)
Each year, a significant number of  individuals over the globe experience  the widespread ailment referred to as  "Eye Flu." However, following a recent  epidemic of conjunctivitis in Delhi,  it is crucial to do a comprehensive  analysis of the tactics employed for  its management. Homeopathic clinics  in Delhi NCR witnessed many such  cases and treated them successfully in  a short span of time. The surge in cases  closely correlated with heavy rainfall,  waterlogging and floods underscoring
Keywords: Management; Epidemic